Dual roles of exostosin glycosyltransferase 1 in Zika virus infection - Jiaxin Ling; Asifa Khan; Matthias Denkewitz; Marco Maccarana; Åke Lundkvist; Jin-Ping Li; Jinlin Li (Virulence)
Many factors involved in heparan sulfate (HS) biosynthesis and metabolism have been reported to play roles in viral infection. However, the detailed mechanisms are still not fully understood. In this study, we report that exostosin glycosyltransferase 1 (EXT1), the HS polymerase, is a critical regulatory factor for Zika virus (ZIKV) infection. Knocking out EXT1 dramatically restricts ZIKV infection, which is not due to the inhibition of virus entry resulting from HS deficiency, but mediated by the downregulation of autophagy. Induction of autophagy promotes ZIKV infection, and attenuated autophagy is found in distinct EXT1 knockout (EXT1-KO) cell lines. Induction of autophagy by rapamycin can relieve the ZIKV production defect in EXT1-KO cells. While over-expressing EXT1 results in the reduction of ZIKV production by targeting the viral envelope (E) protein and non-structural protein NS3 in a proteasome-dependent degradation manner. The different roles of EXT1 in ZIKV infection are further confirmed by the data that knocking down EXT1 at the early stage of ZIKV infection represses viral infection, whereas the increase of ZIKV infection is observed when knocking down EXT1 at the late stage of viral infection. This study discovers previously unrecognized intricate roles of EXT1 in ZIKV infection.